2015
DOI: 10.1038/jid.2014.327
|View full text |Cite
|
Sign up to set email alerts
|

POF1B Localizes to Desmosomes and Regulates Cell Adhesion in Human Intestinal and Keratinocyte Cell Lines

Abstract: By means of morphological and biochemical criteria, we here provide evidence for the localization and function of premature ovarian failure, 1B (POF1B) in desmosomes. In monolayers of Caco-2 intestinal cells and in stratified HaCaT keratinocytes, endogenous POF1B colocalized with desmoplakin at desmosome plaques and in cytoplasmic particles aligned along intermediate filaments (IFs). POF1B predominantly co-fractionated with desmosomes and IF components and exhibited properties characteristic of desmosomes (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…The gene encoding POF1B was critical for ovarian function ( 37 ). However, its impact was also confirmed in the regulation of cell adhesion in human intestinal cell lines ( 38 ). CLMN has been shown to regulate the cell cycle in a report involving neuroblastoma cells ( 39 ).…”
Section: Discussionmentioning
confidence: 93%
“…The gene encoding POF1B was critical for ovarian function ( 37 ). However, its impact was also confirmed in the regulation of cell adhesion in human intestinal cell lines ( 38 ). CLMN has been shown to regulate the cell cycle in a report involving neuroblastoma cells ( 39 ).…”
Section: Discussionmentioning
confidence: 93%
“…Several brush-border membranes such as meprin A and glutamate carboxypeptidase 2 were identified in all experiments. Other proteins related with barrier integrity such as protein POF1B, an important factor in the regulation of cell adhesion, were identified in all experiments. Besides regulators of cell adhesion molecules, haptoglobin, the zonulin precursor, was only identified in the absence of tannins.…”
Section: Resultsmentioning
confidence: 99%
“…showed that the binding of ALDOC to GSK-β leads to the β-Catenin complex collapse and destruction, thus increasing cytoplasmic and nuclear levels of β-catenin in patients with non-small-cell lung cancer ( 35 ). POF1B was located in the critical region for normal ovarian function and participated in encoding premature ovarian failure ( 36 ). Studies predicting the functions of proteins have shown that POF1B had a tight homology relationship with the myosin tail portion of the human myosin protein ( 37 ).…”
Section: Discussionmentioning
confidence: 99%